Oiantheia in between. Cross-border Activities in Ancient Federal Greece - Franchi, Elena (Gerión. Revista de Historia Antigua, 2025)
Oiantheia is a city located on the eastern border of Aitolia having an outlet to the sea and probably a harbour. Their access to the Corinthian Gulf played an essential role in their relations with neighbouring towns and ethne. The town was undoubtedly perceived as Lokrian, yet its location on the border meant there was a pervasive element of Aitolian identity present too. Unsurprisingly, many Aitolian and Lokrian towns in the eastern borderlands with the Ozolian Lokrians had converging interests with their neighbours across the political divide. They exchanged goods locally and regionally, whereas certain surplus goods were even circulated inter-regionally. They also shared a communal enemy in Naupaktos. The cross-border activities and dynamics help to account for the Aitolian-Lokrian synergic integration in the area. The Aitolian koinon set in motion top-down strategies of institutional integration. They also endeavoured to manipulate the symbolic attachment by merging Lokrian genealogies into Aitolian lore. The success of their strategy, however, most likely depended on an effective exploitation of previous political and economic cross-border cooperation, as will be argued in this article.